The Rohingya Refugees and their acculturation process in Bangladesh - Farhana Zamil Tinny,; Abdul Latiff Ahmad,; Shahrul Nazmi Sannusi,; Andika Ab. Wahab, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Acculturation refers to the cultural and psychological changes individuals undergo while interacting with the local community, individually or in a group. The acculturation process may be particularly complex for refugees and asylum seekers, as they leave their home country in search for a better and more secure life while also carrying the unpleasant experiences from their past They experience multiverse differences coming in contact with the host culture in many forms, including religion, food habits, language, and other celebrated cultures in the host community. Rohingya refugees in Bangladesh have also experienced these differences. The study aims to understand the acculturation experience and process of the Rohingya refugees in Bangladesh. This paper addresses John Berry’s model of acculturation to understand how Rohingya refugees adapt to the host community. This study was conducted using semi-structured interviews with 40 Rohingya refugees. The research findings highlight six key stages of acculturation that these Rohingya refugees go through while adapting to the host culture. The identified stages are i) hope, ii) fear of acceptance and uncertainty, iii) trust issues, iv) cultural differences, v) shared value, and vi) interest in the host culture. Despite the cultural and language differences, immediate access to basic needs, food and shelter, safety, and security provided by the Bangladeshi government and the humanitarian workers, including the selfless community support from the host community, facilitated the acculturation process for the Rohingya. This study suggests that sustainable social cohesion can accelerate the acculturation process of the Rohingya refugees in Bangladesh.